Mycobiota evolution during storage of paddy, brown and milled rice in different genotypes - Pinciroli, María (2013)
The rice grain is frequently infected by a series of pathogens (fungi) during its storage, producing damages to the economy and health of humans. The aim of this study was to identify the fungal genera present in different rice genotypes and to quantify their variation during storage. Paddy, brown and milled rice fractions of Nutriar, (N) H329-5(H329) and Don Ignacio genotypes were analyzed at 4, 8 and 12 months of storage. Fungi were identified based on their micromorphological characteristics and colonies. The observed genera according to their frequency were: Alternaria, Nigrospora, Epicoccum, Bipolaris, Curvularia, Cladosporium and Fusarium (field fungi) and Penicillium and Aspergillus (storage fungi). The mycobiota composition was different depending on the grain fraction and the period of storage: field fungi were located in the hulls and bran layers, while storage fungi were mainly in the endosperm. The different genotypes showed different susceptibility to contamination.